Removal of Sb(V) from wastewater via siliceous ferrihydrite: Interactions among ferrihydrite, coprecipitated Si, and adsorbed Sb(V). (March 2022) - Chen, Lei; Han, Yu; Li, Wei; Zhan, Xiaohui; Wang, He; Shi, Chengchao; Sun, Yanping; Shi, Huixiang
Abstract: Although ferrihydrite (Fh) exhibits good Sb(V) adsorption behavior, the instability of its amorphous structure limits its engineering applications. In this study, siliceous ferrihydrite (SiFh) was prepared via coprecipitation to resolve these limitations. X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS), and SiFh aging tests revealed that the growth of Fh particles covered with Fe–O–Si links was inhibited while maintaining their amorphous structure. Meanwhile, the XRD patterns indicated that SiFh maintained excellent stability after five adsorption–desorption cycles. During the aging process, the added Si decreased the electrostatic interaction between SiFh and Sb(V), which weakened the affinity between Sb(V) and Fh; however, most of the Sb(V) still entered the Fe lattice after seven days of aging, which was favorable for Sb(V) recovery during reutilization. Furthermore, Sb(V) adsorbed from the simulated textile wastewater onto SiFh had the highest adsorption energy (Eads ), which meant its unstable inner-sphere complexation on the surface of SiFh. Meanwhile, the presence of SO4 2−, NO3 −, Ca 2+, and Mg 2+ contributed to Sb(V) outer-sphere adsorption. Both of these factors were conducive to Sb(V) desorption. Hence, SiFh is a promising adsorbent owing to its facile preparation process, stability, and optimal regeneration properties. Graphical abstract: Image 1 Highlights: Antimony (V) adsorption on siliceous ferrihydrite (SiFh) was investigated. The added Si decreased the electrostatic interaction between SiFh and Sb(V). Sb(V) was mostly adsorbed via outer-sphere surface complexation in the presence of coexisting ions. Sb(V) removal was impeded by coexisting anions and assisted by cations.